?Continuous Stimulus at The Physiological Blind Spot to Improve Fixation during Perimetry: An Experimental Pilot Study? - Rizvi, Syed Amjad (Pakistan Journal of Ophthalmology, 2006)
Purpose: To evaluate if patients can fixate better during perimetry if a continuous stimulus on the physiological blind spot (CSPBS), present throughout the test, becomes visible to them in real time as soon as fixation is lost, the patient being properly educated accordingly prior to the test. Material and Methods: Subjects between the ages of 20 to 60 years, having no major ocular or systemic disease, underwent a simulation of automated perimetry using a software developed by the Author, with a 21-inch personal computer monitor used as a campimeter. There was an option in the software whether or not a conspicuous CSPBS was presented throughout the test. Fixation losses were recorded by Heijl-Krakau method. Patients who consistently had fixation loss of more then 30% without a CSPBS were subsequently tested with the CSPBS present during the test. Results: 9 subjects out of 50 initially tested (18%), persistently had more then 30% fixation losses with out CSPBS during the test. Seven out of these 9 (14% of the total) showed improvement in fixation when tested with a CSPBS. The remaining 2 (4% of the total) had poor fixation in the presence of CSPBS also. Conclusion: CSPBS present throughout an automated perimetry test can potentially improve fixation and should be evaluated on larger scale.